HAEMATOLOGICAL CHANGES IN MALARIA INFECTION AMONG PREGNANT WOMEN IN SOKOTO METROPOLIS NIGERIA - Garba, I.; Umar, A. I.; Tijjani, M. B.; Aliyu, M. S.; Muhammad, H. I. D.; Raji, M. I. O.; Fana, S. A.; Thompson, J. (FUDMA JOURNAL OF SCIENCES, 2023)
One of the most fatal illnesses that affects humans is malaria. This study was aimed at determining the haematological changes in pregnant malaria-infected women. One hundred blood samples were taken from pregnant women between the ages of 15 and 45. Samples were screened using standard methods. Out of 100 pregnant women examined, 28% had parasites whereas 72% did not. Based on age, women between the ages of 36 and 40 had the highest prevalence of malaria during pregnancy (33.3%). The haematological parameters of pregnant women with malaria infection and those who were not infected did not differ significantly, according to a Student T-test. Pregnant women's mean Packed cell volume was 28.43% compared to pregnant women who weren't sick of malaria.  The mean value of  Red blood cell in infected pregnant women 3.45x1012/l  was lower than the non parasitaemic pregnant women 3.53x1012/l, the mean value of White blood cell  6.89x109/l  was in the normal range for both infected and non-infected pregnant women, Red cell indices (MCH, MCHC) were low 27.00pg, 33.80pg in malaria infected pregnant women than non-infected pregnant women 28.23pg, 34.35pg, the mean value of MCV(82.02fl)  was higher in pregnant women than the non- infected pregnant women (81.83fl), the mean  Platelet value (217.1x109/l) was high in infected pregnant women than non-malaria pregnant women (213.1x109/l). Neutrophil and Lymphocyte were (60.92%, 27.49%) low in malaria infected pregnant women than the non parasitaemic (61.69%, 28.73%). Screening for malaria and haematological alterations in pregnancy will help in reducing the scourge of malaria infection.
Keywords: Haematological; Changes; Malaria infection; Pregnant women; Sokoto